2008
DOI: 10.1387/ijdb.072538dc
|View full text |Cite
|
Sign up to set email alerts
|

Participation of cysteine-rich secretory proteins (CRISP) in mammalian sperm-egg interaction

Abstract: Mammalian fertilization is a complex multi-step process mediated by different molecules present on both gametes. CRISP1 (cysteine-rich secretory protein 1) is an epididymal protein thought to participate in gamete fusion through its binding to egg-complementary sites. Structure-function studies using recombinant fragments of CRISP1 as well as synthetic peptides reveal that its egg-binding ability resides in a 12 amino acid region corresponding to an evolutionary conserved motif of the CRISP family, named Signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 49 publications
2
48
0
1
Order By: Relevance
“…Little is known about the function of the mammalian CRISPs; however, CRISP1 and CRISP2 are known to be involved in various steps in reproduction (24). The C-terminal domain of CRISP2 has been shown to interact with calcium channels (25) and to bind a kinase present in the acrosome of mouse sperm (26).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the function of the mammalian CRISPs; however, CRISP1 and CRISP2 are known to be involved in various steps in reproduction (24). The C-terminal domain of CRISP2 has been shown to interact with calcium channels (25) and to bind a kinase present in the acrosome of mouse sperm (26).…”
Section: Discussionmentioning
confidence: 99%
“…CRISP1 and CRISP4 are enriched in the epididymis, CRISP2 is exclusively in developing spermatids in the testes, and CRISP3 is in wider tissue distribution than the other CRISPs. 28,29 When recombinant mouse CRISP1 and CRISP2 were added to eggs, they specifically bound to the fusogenic area of mouse eggs. The antibodies against these proteins significantly inhibit the fertilization ratio.…”
Section: -11mentioning
confidence: 99%
“…These proteins have been implicated as essential contributors during sperm egg fusion. Results of experiments conducted by Cohen et al (2008) showed appearance of CRISP1 involvement in the first step of sperm binding to the zona pellucida. They also observed that sperm testicular CRISP2 is also able to bind to the egg surface which is indicative of its necessity in gamete fusion.…”
Section: Proteome Of Spermatozoamentioning
confidence: 97%